2020
DOI: 10.2298/gensr2001229a
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic content, antioxidant, antibacterial and antifungal activities, FT-IR analyses of Brassica oleracea L. var. acephala and Ornithogalum umbellatum L.

Abstract: Brassica oleracea var. acephala and Ornithogalum umbellatum are two plant species which belong Brassicaceae and Liliaceae, respectively. Both of them are used as food and medicinally. O. umbellatum is used as anticancer, diuretic anti anti emetic. B. oleracea var. acephala is used for gastritis, gastric and duodenal ulcers and preventing some cancer forms such as stomach cancer, breast cancer and lung cancer. The aim of this research was to search antioxidant, antibacterial and antifungal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With a powerful antioxidant activity of 88.43 µg/g ascorbic acid equivalents. In another study by Aydin (2020), antioxidant, antibacterial activity (against Salmonella enterica, Enterococcus faecalis, Enterobacter aerogenes, and Proteus vulgaris ), and antifungal (against Candida albicans, Candida tropicalis, and Saccharomyces cerevisiae ) were found in kale extracts, obtained with ethanol as a solvent by means of the soxhlet methodology. Highlighting a greater antimicrobial activity against fungi than against bacteria.…”
Section: Extraction Of Bioactive Compoundsmentioning
confidence: 99%
“…With a powerful antioxidant activity of 88.43 µg/g ascorbic acid equivalents. In another study by Aydin (2020), antioxidant, antibacterial activity (against Salmonella enterica, Enterococcus faecalis, Enterobacter aerogenes, and Proteus vulgaris ), and antifungal (against Candida albicans, Candida tropicalis, and Saccharomyces cerevisiae ) were found in kale extracts, obtained with ethanol as a solvent by means of the soxhlet methodology. Highlighting a greater antimicrobial activity against fungi than against bacteria.…”
Section: Extraction Of Bioactive Compoundsmentioning
confidence: 99%
“…It was reported that DPPH IC50 values of aerial parts and bulb of Ornithogalum sintenisii at flowering stage was found to be 368±15 and 669±25 µg/mL, respectively (Ebrahimzadeh et al, 2010). However, DPPH % inhibition of O. umbellatum stem and flower parts for concentration of 200 µg/mL were determined 24.92±0.012 % and 15.31±0.002 %, respectively (Aydın, 2020). In a recent study, methanol and water extracts of bulb of Ornithogalum narbonense were calculated as 12.60±0.30 and 4.02±0.55 mg TE/g extract, respectively for DPPH (Zengin et al, 2015).…”
Section: Resultsmentioning
confidence: 95%